1993
DOI: 10.1507/endocrj.40.185
|View full text |Cite
|
Sign up to set email alerts
|

Comparison Between Insulin-Like Growth Factor-I(IGF-I) and IGF Binding Protein-3(IGFBP-3) Measurement in the Diagnosis of Growth Hormone Deficiency.

Abstract: Abstract. To analyze the utility of insulin-like growth factor-I (IGF-I) and insulin-like growth factor binding protein-3 (IGFBP-3) radioimmunoassay in the diagnosis of growth hormone deficiency (GHD) we measured IGF-I and IGFBP-3 in sera from normal children (n=309), short children (n=99) and patients with GHD (n=73). In 80% and 93% of classical GHD (cGHD), IGF-I and IGFBP-3 levels, respectively, were below the age-related cutoff levels (lower limit). In 81% and 88% of normal short children (NS), IGF-I and IG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
1
1

Year Published

1995
1995
2019
2019

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 10 publications
0
19
1
1
Order By: Relevance
“…To our knowledge, only one report has been published on the value of IGF-I and IGFBP-3 in the prediction of growth response to GH therapy [16]. In this study, a negative relationship between IGFBP-3 and the increment in height velocity was found, but this was caused mainly by the subgroup of ‘complete’ GHD children (maximal GH levels after provocation <10 mU/l).…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…To our knowledge, only one report has been published on the value of IGF-I and IGFBP-3 in the prediction of growth response to GH therapy [16]. In this study, a negative relationship between IGFBP-3 and the increment in height velocity was found, but this was caused mainly by the subgroup of ‘complete’ GHD children (maximal GH levels after provocation <10 mU/l).…”
Section: Discussionmentioning
confidence: 55%
“…The serum concentrations of these proteins are GH-dependent and several studies have shown that low levels of serum IGF-I, IGF-II and IGFBP-3 and high serum IGFBP-2 levels may be predictive for GHD, although not all studies have come to similar conclusions [4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21]. Theoretically, the biological response to GH treatment could be used as the final confirmation of the diagnosis of GHD, as children with severe GHD on the average accelerate their growth more than children with a less severe deficiency and considerably more than children with idiopathic short stature (ISS) [22].…”
Section: Introductionmentioning
confidence: 99%
“…IGF-I action is also critically modulated by specific binding proteins, among which IGF binding protein 3 (IGFBP-3) is the most abundant circulating form. IGFBP-3 is GH-dependent [15]and has been considered to be another marker of GH secretion, although it is less sensitive than IGF-I [8, 22, 23, 24, 25]. IGF-I is generally measured as total circulating levels, although free IGF-I levels can also be measured [12, 26].…”
Section: Introductionmentioning
confidence: 99%
“…Serum and plasma were obtained after 8-10 h fasting in the morning. In these subjects, the free form of IGF-I (free IGF-I), the total IGF-I (total IGF-I: free plus complexed form of IGF-I) , and IGFBP-3 were measured, as previously described [3,4]. The Zscores of free IGF-I, total IGF-I, and IGFBP-3 were calculated by using age-matched normal values [4, 5, our unpublished data].…”
Section: Methodsmentioning
confidence: 99%